ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2013-2016 - Retnowulan, 13.05.52.0007; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2018)
Analysis Of Factors That Affect The Performance Of Financial Statements On Manufacturing Companies Listed In Indonesia Stock Exchange 2013-2016. The population in this research is all companies that move in the manufacturing sector listed in Indonesia Stock Exchange (BEI) year 2013-2016. Sampling technique is purposive sampling with criteria: (1) The financial statements of a manufacturing company having financial data relating othere search variable in full. (2) The manufacturing companyis not in a loss state for the year 2013-2016. (3) The Company presents the financial statements in rupiah currency. The results show that audit tenure, institutional ownership, managerial ownership, independent commissioner, and KAP size have no effect on the integrity of financial statements. While the audit committee affects the integrity of financial statements.Keywords: Tenure Auditee, Institutional Ownership, Managerial Ownership, Audit Committee, Independent Commissioner, CAP Size Against Integrity of Financial Statements.